To Change is Human: "Abnormal" Reliable Change Memory Scores are Common in Healthy Adults and Older Adults. (24th November 2016) - Brooks, Brian L.; Holdnack, James A.; Iverson, Grant L.
Abstract : Objective: The rate at which people obtain reliably improved or declined cognitive test scores when retested, in the absence of a change in clinical condition, is largely unknown. The purpose of this study was to illustrate the prevalence of statistically reliable change scores on memory test batteries in healthy adults and older adults. Method: Participants included three adult and older adult test-retest samples from memory test batteries. Reliable change scores (reliable change index with 90% confidence interval and practice effects) were calculated for the indexes and subtests of each battery. Multivariate analyses involved calculating the frequencies of healthy people obtaining one or more reliably declined or one or more reliably improved scores when considering all change scores simultaneously within each battery. Results: Across all batteries, having one or more reliably changed index or subtest score on retest was common. With most batteries, having two or more reliably changed scores was uncommon. Those with higher intellectual abilities were more likely to have a change on retest; however, no significant differences in base rates were found based on education level, sex, or ethnic minority status. Those older adults who did not have any low memory scores were more likely to improve than decline on retest. Conclusions: Having a single reliably changed score on retest is common when interpreting a battery of memory measures. This has implications for determining cognitive decline and cognitive recovery, suggesting that multivariate interpretation is necessary.